ChemInform Abstract: One‐Pot Silyl Ketene Acetal‐Formation Mukaiyama—Mannich Additions to Imines Mediated by Trimethylsilyl Trifluoromethanesulfonate. Issue 15 (24th March 2016) - Downey, C. Wade; Ingersoll, Jared A.; Glist, Hadleigh M.; Dombrowski, Carolyn M.; Barnett, Adam T.
Abstract: Thioesters, esters, N‐arylamides and ketones react successfully with N‐arylimines if a Tms‐O‐Tf/trialkylamine mixture is used.